Analysis of pulmonary nodules in patients with high-grade soft tissue sarcomas. - Tomoki Nakamura; Akihiko Matsumine; Miki Matsusaka; Keitaro Mizumoto; Mayuko Mori; Tomoya Yoshizaki; Takao Matsubara; Kunihiro Asanuma; Akihiro Sudo (PLoS ONE)
Nowadays, small pulmonary nodules are easily detectable in patients with soft tissue sarcomas (STSs) because of highly improved computed tomography (CT) technologies. The purpose of this study was to determine the frequency and significance of the pulmonary nodules detected by CT in high-grade STS patients. 124 patients with high-grade STS were retrospectively reviewed. There were 72 males (57%) and 52 females (43%). Patients' average age was 61 years (median (quartiles) 66 years (48-75), range 8-94 years). Pulmonary nodules were detected in 49 (39.5%) of 124 patients by CT scanning at first presentation. Of 49 patients with nodules at first presentation, 34 (69.4%) had benign lesions, and 13 (26.5%) had metastatic nodules. One patient (2%) had primary lung cancer and the remaining one with one nodule could not be definitively diagnosed due to a short follow-up time. 30 patients (24.1%) of 124 patients developed pulmonary nodules during their clinical progression. Seven (23.3%) had benign lesions, whereas 21 (70%) had metastatic lesions. Primary lung cancer was detected in two patients (6.7%). The size and timing of detection of a pulmonary nodule significantly affected the final clinical diagnosisby multivariate analysis. We conclude that pulmonary nodules can be detected highly frequently in patients with high-grade STSs because of improved CT technologies. Careful follow-up is needed if nodules are detected after initial treatment or during the clinical course of the disease.